Factors influencing retirement decisions among Malaysian university civil servants - Mat, Zawiah; Abdul Hamid, Nor Fazilah; Jaffri, Ani (Human Resource Management Academic Research Society, 2024)
Civil servants are essential assets in the execution of the national development agenda, aligning with the nation’s vision and objectives to foster a workforce that is competent, knowledgeable, and highly skilled. Within this framework, civil servants are granted the option of either compulsory or voluntary retirement, as delineated by the Treasury Circular and the Public Service Department (JPA). This study examines the factors that influence retirement decisions among civil servants in Malaysian public universities. A qualitative research methodology was employed, utilizing semi structured interviews for data collection. The sample included nine participants from Melaka Public University, selected through purposive sampling to represent various categories of positions, including academic, administrative, and executive roles. Thematic analysis was conducted to interpret the data. The findings indicate that three primary factors contribute to voluntary retirement: healthrelated issues, personal motivations, and environmental influences. This research is vital for enhancing the civil service staffing framework and serves as a valuable reference for the Human Resources division within Malaysian higher education institutions.